Regulation and Functional Complexity of the Chlorophyll-Binding Protein IsiA - Jia, Anqi; Zheng, Yanli; Chen, Hui; Wang, Qiang (Frontiers in Microbiology, 2021)
As the oldest known lineage of oxygen-releasing photosynthetic organisms, cyanobacteria play the key roles in helping shaping the ecology of Earth. Iron is an ideal transition metal for redox reactions in biological systems. Cyanobacteria frequently encounter iron deficiency due to the environmental oxidation of ferrous ions to ferric ions, which are highly insoluble at physiological pH. A series of responses, including architectural changes to the photosynthetic membranes, allow cyanobacteria to withstand this condition and maintain photosynthesis. Iron-stress-induced protein A (IsiA) is homologous to the cyanobacterial chlorophyll (Chl)-binding protein, photosystem II core antenna protein CP43. IsiA is the major Chl-containing protein in iron-starved cyanobacteria, binding up to 50% of the Chl in these cells, and this Chl can be released from IsiA for the reconstruction of photosystems during the recovery from iron limitation. The pigment–protein complex (CPVI-4) encoded by isiA was identified and found to be expressed under iron-deficient conditions nearly 30 years ago. However, its precise function is unknown, partially due to its complex regulation; isiA expression is induced by various types of stresses and abnormal physiological states besides iron deficiency. Furthermore, IsiA forms a range of complexes that perform different functions. In this article, we describe progress in understanding the regulation and functions of IsiA based on laboratory research using model cyanobacteria.